Non-linear association of birth weight with lung function and risk of asthma: A population-based study - Yang, Meng; Mei, Hong; Du, Juan; Yu, Linling; Hu, Liqin; Xiao, Han (Frontiers in Public Health, 2022)
Background: The impact of birth weight on lung function and risk of asthma remains contentious, with limited evidence on nonlinear association. Our aim was to investigate the specific association of birth weight with lung function and the risk of asthma in children. Methods: We performed cross-sectional analyses of 3,295 children aged 6-15 years who participated in the 2007-2012 National Health and Nutrition Examination Survey (NHANES). After controlling for potential covariates, the linear and nonlinear association of birth weight with lung function metrics and the risk of asthma were evaluated by a generalized linear model and generalized additive model, respectively. Results: We observed a nonlinear association of birth weight with FEV1 %predicted, FEV1/FVC %predicted and FEF25-75 %predicted (P for nonlinearity was 0.0029, 0.0059 and 0.0027, respectively). Further threshold effect analysis of birth weight on lung function detected the turning point for birth weight was 3.6 kg. When the birth weight was <3.6 kg, birth weight was significantly positively associated with FEV1 %predicted, FEV1/FVC %predicted and FEF25-75 %predicted. However, a negative association was found when the birth weight was ≥3.6 kg. These results were consistent in the stratified and sensitivity analyses. Additionally, a possible nonlinear relationship was also detected between birth weight and the risk of asthma. Conclusions: Our findings provided new insight into the association of birth weight with lung function. Future studies are warranted to confirm the present findings and understand the clinical significance.